Preliminary study on mesenchymal stem cells in repairing nerve injury in pelvic floor denervation - Zhang, Guorui; Dai, Yuxin; Lang, Jinghe (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction Nerve injury is considered one of the causes of pelvic floor dysfunction. Mesenchymal stem cells (MSCs) transplantation provides new possibilities for refractory degenerative diseases. This study aimed to explore the possibility and strategy of mesenchymal stem cells in treating pelvic floor dysfunction nerve injury. Methods MSCs were isolated from human adipose tissue and cultured. A MSCs suspension (40 µl at 5×107/ml) was loaded on a gelatin scaffold. A rat model of anterior vaginal wall nerve injury was established by bilateral pudendal nerve denervation. The nerve tissue repair effect of mesenchymal stem cells transplanted into the anterior vaginal wall of a rat model was explored and compared in the following three groups: blank gelatin scaffold group (GS group), mesenchymal stem cell injection group (MSC group), and mesenchymal stem cells loaded on the gelatin scaffold group (MSC-GS group). Nerve fiber counting under a microscope and mRNA expression of neural markers were tested. Moreover, mesenchymal stem cells were induced into neural stem cells in vitro, and their therapeutic effect was explored. Results Rat models of anterior vaginal wall nerve injury induced by bilateral pudendal nerve denervation showed a decreased number of nerve fibers in the anterior vaginal wall. qRT-PCR revealed that the content of neurons and nerve fibers in the rat model began to decrease 1 week after the operation and this could continue for 3 months. In vivo experiments showed that MSC transplantation improved the nerve content, and MSCs loaded on the gelatin scaffold had an even better effect. mRNA expression analysis demonstrated that MSCs loaded on gelatin scaffolds induced a higher and earlier gene expression of neuron-related markers. Induced neural stem cell transplantation was superior in improving the nerve content and upregulating the mRNA expression of neuron-related markers in the early stage. Conclusions MSCs transplantation showed a promising repair capacity for nerve damage in the pelvic floor. The supporting role of gelatin scaffolds might promote and strengthen the nerve repair ability at an early stage. Preinduction schemes could provide an improved regenerative medicine strategy for innervation recovery and functional restoration in pelvic floor disorders in the future.